Development and Evaluation of Android Based Notification System to Determine Patient's Medicine for Pharmaceutical Clinic - Imam Riadi; Sri Winiarti; Herman Yuliansyah (IAES Indonesia Section, 2017)
The development of science in the field of health clinical pharmacy grows rapidly in recent years. Based on the data from information was obtained that needs to be done a reparation a learning process in clinical pharmacy to produce them who as requested by users pharmaceutical graduates. According to the results of the information there is a problem that in conducting the process of determining the pharmacys drug it can be made a mistake, especially in patients who have complications disease. The process of checking conducted repeatedly to make sure a medicine that is concocted in accordance with a list of the acts of treat a patient, while patient data not yet integrated into a system that could help them in analysis and determine a drug that in accordance. Notification system that developed using android platform this, the hope can become the tools in the form of a system that can give notification to the farmasis easily accessible at any time through gadgets. Based on the results of testing with the methods alpha test can be concluded the number of feasibility this system reached 88.75%. Thus notification system in the determination of medicine patients rule based as a medium learn students pharmaceutical clinic worthy to used.